The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.4049/jimmunol.176.12.7636
|View full text |Cite
|
Sign up to set email alerts
|

The Envelope Protein of a Human Endogenous Retrovirus-W Family Activates Innate Immunity through CD14/TLR4 and Promotes Th1-Like Responses

Abstract: Multiple sclerosis-associated retroviral element (MSRV) is a retroviral element, the sequence of which served to define the W family of human endogenous retroviruses. MSRV viral particles display proinflammatory activities both in vitro in human mononuclear cell cultures and in vivo in a humanized SCID mice model. To understand the molecular basis of such properties, we have investigated the inflammatory potential of the surface unit of the MSRV envelope protein (ENV-SU), the fraction that is poised to natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
254
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 238 publications
(280 citation statements)
references
References 48 publications
(41 reference statements)
6
254
1
6
Order By: Relevance
“…MSRV-Env activates Toll-like receptor 4 (TLR4) and has a pro-inflammatory effect mediated through its interaction with TLR4 in peripheral blood mononuclear cell (PBMC) cultures (Rolland et al, 2006). Another effect of MSRV-Env is the blockade of the oligodendrocyte differentiation necessary for the remyelination process, also mediated by an interaction with TLR4 on oligodendrocyte precursor cells (OPCs) (Kremer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSRV-Env activates Toll-like receptor 4 (TLR4) and has a pro-inflammatory effect mediated through its interaction with TLR4 in peripheral blood mononuclear cell (PBMC) cultures (Rolland et al, 2006). Another effect of MSRV-Env is the blockade of the oligodendrocyte differentiation necessary for the remyelination process, also mediated by an interaction with TLR4 on oligodendrocyte precursor cells (OPCs) (Kremer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinical studies showed that GNbAC1 neutralizes the MSRV-Env target (Rolland et al, 2006;Kremer et al, 2014). GNbAC1 had been studied first in a phase I clinical trial in 33 healthy subjects, showing a good safety as well as a linear pharmacokinetics (Curtin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Це опосередковано взаємодією ендогенних ретровірусів з Толл-подібним рецептором 4 (TLR4) і CD14-корецептором [15]. TLR4 є одним із основних образ-розпізнавальних рецепторів, що віді-грають центральну роль в ініціації вродженого імунітету проти мікробних патогенів.…”
Section: вступunclassified
“…TLR4 активуються в гліаль-них клітинах і лімфоцитах, які проникли в ЦНС у від-повідь на запалення, що викликане інфекційними аген-тами, травмою тканин або автоімунним процесом [16]. Окрім того, активований TLR4 здійснює виражений інгібуючий вплив на ріст клітин-попередників оліго-дендроцитів (основних продуцентів мієліну) [15].…”
Section: вступunclassified
“…D'autres études ont par la suite exploré et dévoilé progressivement les caractéristiques génétiques et biologiques inattendues de cet HERV. Ainsi, les séquences HERV-W, isolées de particules rétrovirales provenant de cultures de cellules de patients atteints de SEP, codent une protéine d'enveloppe biologiquement active (MSRV-Env) qui est capable d'activer les cascades physiopathologiques à l'origine des signes pathognomoniques de la SEP. En particulier, MSRV-Env peut induire une activation de type superantigène (activation polyclonale, donc disproportionnée, indépendante de la spécificité de l'antigène reconnu) des lymphocytes T [28], elle-même conditionnée en amont à une stimulation de l'immunité innée impliquant le récepteur TLR4 (Tolllike receptor 4) avec des effets pro-inflammatoires [29]. MSRV-Env peut promouvoir l'activation des macrophages, la différenciation des cellules …”
Section: La Sclérose Latérale Amyotrophiqueunclassified